Sacrifice, violence, and ideology among the Moche : the rise of social complexity in ancient Peru - Bourget, Steve, 1956- (William & Bettye Nowlin series in art, history, and culture of the Western Hemisphere., 2016)
"In a special precinct dedicated to ritual sacrifice at Huaca de la Luna on the north coast of Peru, about seventy-five men were killed and dismembered, their remains and body parts then carefully rearranged and left on the ground with numerous offerings. The discovery of this large sacrificial site--one of the most important sites of this type in the Americas--raises fundamental questions. Why was human sacrifice so central to Moche ideology and religion? And why is sacrifice so intimately related to the notions of warfare and capture? In this pioneering book, Steve Bourget marshals all the currently available information from the archaeology and visual culture of Huaca de la Luna as he seeks to understand the centrality of human sacrifice in Moche ideology and, more broadly, the role(s) of violence in the development of social complexity. He begins by providing a fully documented account of the archaeological contexts, demonstrating how closely interrelated these contexts are to the rest of Moche material culture, including its iconography, the regalia of its elite, and its monumental architecture. Bourget then probes the possible meanings of ritual violence and human sacrifice and their intimate connections with concepts of divinity, ancestry, and foreignness. He builds a convincing case that the iconography of ritual violence and the practice of human sacrifice at all the principal Moche ceremonial centers were the main devices used in the establishment and development of the Moche state."--Publisher's description